Debate: Are cluster headache and migraine distinct headache disorders? - Al-Karagholi, Mohammad Al-Mahdi; Peng, Kuan-Po; Petersen, Anja Sofie; De Boer, Irene; Terwindt, Gisela M.; Ashina, Messoud (Journal of headache and pain, 2022)
Cluster headache and migraine are regarded as distinct primary headaches. While cluster headache and migraine differ in multiple aspects such as gender-related and headache specific features (e.g., attack duration and frequency), both show clinical similarities in trigger factors (e.g., alcohol) and treatment response (e.g., triptans). Here, we review the similarities and differences in anatomy and pathophysiology that underlie cluster headache and migraine, discuss whether cluster headache and migraine should indeed be considered as two distinct primary headaches, and propose recommendations for future studies. Graphical Abstract Video recording of the debate held at the 1st International Conference on Advances in Migraine Sciences (ICAMS 2022, Copenhagen, Denmark) is available at https://www.youtube.com/watch?v=uUimmnDVTTE .